Reverse “L” surgical approach for the management of giant tumors of the cervicothoracic junction - Zhong, Yuan; Yang, Xuhui; Jiang, Lianyong; Hu, Rui; Jiang, Zhaolei; Wang, Mingsong (Journal of thoracic disease, 2020)
An isolated cervical or thoracic surgical approach provides insufficient exposure for achieving complete resection of tumors of the cervicothoracic junction. This study examines reverse "L" thoracotomy as a surgical approach to these tumors. Additionally, the feasibility, safety, and effectiveness of reverse "L" surgical incision for tumor resection was also analyzed. Patients with cervicothoracic tumors were identified from an internal database. Subjects were selected on the basis of undergoing reverse "L" thoracotomy from August 2014 to August 2018. The tumor characteristics, surgical technique, completeness of resection, morbidity, and patient outcome were reviewed. All patients successfully underwent resection through reverse "L" surgical approach. No patients needed to undergo full sternotomy. There were 6 neurogenic tumors, 4 thyroid adenocarcinomas, 4 bronchogenic tumors, and 7 other cases in the study. The median operative time was 191.0 min (range, 113.0-348.0 min) and postoperative in-hospital stay ranged from 3 to 7 days. Horner syndrome was observed in 1 case. Hoarseness and lymphatic leakage were evident in 3 and 1 case(s), respectively. Hemidiaphragm paralysis was observed in 1 case. Three cases were unsuccessful in achieving R0 resection. The duration of follow-up ranged from 6 to 42 months. Eleven of 13 patients who underwent resection had no evidence of tumor recurrence. Two patients with metastatic disease died of distant progression within 15 months. Applying reverse "L" surgical approach is safe, feasible, and effective for the resection of giant tumors of the cervicothoracic junction.